Microbial transformation of glycyrrhizic acid and identification of their secondary metabolites through LCMS and NMR / Fatin Farhanah Jamil - Jamil, Fatin Farhanah (2009)
The mam objective of our study is to be able to observe the process of microbial transformation on biologically active compound, glycyrrhizic acid, and to identify the secondary metabolites generated when glycyrrhizic acid is subjected to microbial transformation by using HPLC and NMR. In achieving the objectives of our study, there are two particular steps involve which were primary screening of secondary metabolites and large scale production of secondary metabolites. Primary screening was done in order to check which fungi transform the most potential and abundant secondary metabolites from glycyrrhizic acid. After the first step was performed, Trichothecium roseum was chosen as the fungi of interest for the large scale production and we was able to identify few secondary metabolites generated from Trichothecium roseum from HPLC chromatogram observed. Our research however was limited to HPLC identification. Structural elucidation by NMR cannot be done because of time limitation.